(untitled) (Fiep Bulletin - online, 2024)
Introduction: This research presents an analysis of the perspective of undergraduate students in physical education at the Federal University of Paraíba on judo as a school content. The Objective is to relate experiences of judo during teacher training, with future pedagogical attitudes to be adopted, understand expectations and identify difficulties regarding this fight in the school environment. Methods: the study is qualitative in nature, with a descriptive-explanatory typology, with a transversal temporal cut. The data collection instrument used was semi-structured interviews, which were based on discourse analysis. 30 physical education students enrolled at UFPB, who had already studied judo, participated in the investigation. Results: the reports mentioned factors such as attention, concentration, cooperation, respect and self-defense arising from the practice of the sport. Furthermore, when asking about expectations, contexts were identified that could result in this subject not being approached, such as the (pre)concept of violence, class avoidance justified by the use of electronic devices and social imperatives such as the conception of gender, which is still present today. Conclusion: this research becomes relevant when referring to the importance of judo in the school environment, also contributing to the main aspects of the study that report the students’ perspectives in the speeches obtained, analyzed and exposed, becoming an instrument for derivative research and analysis . It is expected to contribute to reflections on didactic-pedagogical means during teacher training, enabling the future teacher to have confidence and mastery of judo teaching so that this sport is present in physical education classes.